Producing race disparities: a study of drug arrests across place and race - Gaston, Shytierra (Criminology, 2019)
In studies of race disparities in policing, scholars generally employ quantitative methodologies with the goal of determining whether race disparities exist or, in fewer instances, of ruling out correlates. Yet, lacking from theoretical and empirical efforts is an elucidation of how and why on‐the‐ground policing produces race disparities that are justified in legal, race‐neutral terms. To address this knowledge gap, I analyze officers’ self‐reported accounts of their enforcement activities, justifications, and decision‐making in a representative sample of 300 official reports of drug arrests made in St. Louis from 2009 to 2013. These accounts are analyzed across neighborhood racial contexts and arrestee race, revealing important differences that help illuminate the race disparity problem. Unlike drug arrests in White neighborhoods or of White citizens that primarily stem from reactive policing, drug arrests in Black and racially mixed neighborhoods and of Black citizens result from officers’ greater use of discretionary stops based on neighborhood conditions, suspicion of ambiguous demeanor, or minor infractions. During such stops, officers’ discovery of drug possession often results from discretionary Terry frisks or searches incident to arrests for outstanding bench warrants. These findings fill important theoretical and empirical gaps and have implications for reforms toward racially just policing.